Pollutant Removal and Peak Flow Mitigation by a Bioretention Cell in Urban Charlotte, N.C - Hunt, W. F; Smith, J. T; Jadlocki, S. J; Hathaway, J. M; Eubanks, P. R (Journal of environmental engineering (New York, N.Y.), 2008)
Bioretention is a stormwater treatment practice that has gained popularity due to its aesthetics, potential to reduce flooding, and early documented improvements to stormwater quality. A bioretention cell in an urban setting was examined in Charlotte, N.C. from 2004 to 2006. Flow-weighted, composite water quality samples were collected for 23 events and analyzed for TKN, N H4 -N , N O2-3 -N , TP, TSS, BOD-5, Cu, Zn, Fe, and Pb. Grab samples were collected from 19 storms for fecal coliform and 14 events for Escherichia coli (E. coli). There were significant reductions (p<0.05) in the concentrations of TN, TKN, N H4 -N , BOD-5, fecal coliform, E. Coli, TSS, Cu, Zn, and Pb. Iron concentrations significantly increased (p<0.05) . N O2-3 -N concentrations were essentially unchanged. Efficiency ratios for TN, TKN, N H4 -N , TP, and TSS were 0.32, 0.44, 0.73, 0.31, and 0.60, respectively. Fecal coliform and E. coli efficiency ratios were 0.69 and 0.71, respectively. Efficiency ratios for Zn, Cu, and Pb were 0.77, 0.54, and 0.31, respectively. Concentrations of Fe increased by 330%. The peak outflow of the bioretention cell for 16 storms with less than 42 mm of rainfall was at least 96.5% less than the peak inflow, with a mean peak flow reduction being 99%. These results indicated that in an urban environment, bioretention systems can reduce concentrations of most target pollutants, including pathogenic bacteria indicator species. Additionally, bioretention can effectively reduce peak runoff from small to midsize storm events.